Marketing Mix and Psychology on Purchase Decision and Repurchase in the Creative Industry - Puspita, Dyah Rangga (Interdisciplinary Social Studies, 2022)
Background: Some factors that affect the success of the creative economy such as purchasing by consumers include the marketing mix’ influence, psychological influences, socio-cultural influences, and the influence of the situation/environment. Satisfaction with the first purchase is a factor that affects the repurchase intention. Aim: This research aimed at discovering the influence of mixed marketing and psychological condition on purchase decisions and repurchase for the creative industry. Method: This is explanatory research. The approach used is quantitative, with a sample number of 91 out of 162 populations. Primary data collection using questionnaires was conducted. The data analysis used in this study is descriptive analysis and path analysis. Findings: The first hypothesis H1 received is "Marketing mix (X1) has a significant effect on purchasing decisions (Y1)". For H2 received, namely "Psychology (X2) has a significant effect on purchasing decisions (Y1)". Then for H3 received, namely "Marketing mix (X1) has a significant effect on the repurchase (Y2)". Furthermore, for H4 received, namely "Psychological (X2) has a significant effect on the repurchase (Y2)". For H5 received, namely "Purchase decision (Y1) has a significant effect on the repurchase (Y2)". The results of the path analysis showed that there was an influence between the marketing mix and the purchase decision by 30.2%, psychology to the purchase decision by 20.9%, the marketing mix on the repurchase by 20.3%, the psychological on the repurchase by 28.5% and the purchase decision on the repurchase by 36.4%.